Potential of cellulose tri acetate (CTA) membrane for seawater treatment by forward osmosis - Chiang, Xin Yi (2017)
Nowadays, the increased of human population and rapid industrial growth in most parts of the word caused insufficient clean water supply and water scarcity. Therefore the depletion of resources of water encouraged us to find new resources for clean water supply. Forward osmosis (FO) which used in desalination of seawater by using low energy consumed and low cost needed become more potential process to treat in desalination of seawater. This research focused on the seawater treatment by forward osmosis by Cellulose Tri Acetate (CTA) Membrane. Sodium sulphate was used as draw solution because of less toxicity and easily recovery after forward osmosis process. Synthetic seawater, NaCl with concentration of 35g/L was used as feed solution. This research was conducted based on different concentrations of draw solution (1.0M, 1.25M, 1.50M, 1.75M and 2.0M) and pH (3, 7 and 9) which will impact the water flux and reverse salt flux (RSF). Besides that, the effect of orientation of CTA membrane in the mode of active layer face draw solution (AL-DS) and active layer face feed solution (AL-FS) were also investigated. After optimum parameters were obtained, treatment on real seawater was conducted and the results were compared with synthetic seawater. To observe that, 1.75M of sodium sulphate produced highest water flux at value 1.07 E-04 m3/m2.min and optimum RSF 6.44 GMH at pH 7. Good performance of FO were shown in the orientation AL-DS of CTA membrane. Besides that, real seawater treatment has lower water flux (7.00 E-05 m3/m2.min) and RSF (3.68 GMH) than synthetic seawater. In conclusion, 1.75M and pH 7 of sodium sulphate as draw solution in AL-DS orientation of CTA membrane showed the optimum performance of FO.